1962
DOI: 10.1172/jci104531
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Human Myocardial Oxygen Extraction During Rest and Exercise*

Abstract: Myocardial oxygen requirements are met by coronary blood flow and oxygen extraction from the arterial blood. The myocardial oxygen extraction coefficient (1) expresses the fraction of available oxygen in arterial blood removed by the myocardium: coronary A-Vo2/Ao2 X 100 = myocardial extraction percentage. Myocardial oxygen extraction during rest is approximately 70 to 75 per cent, exceeding that of all other organs (1, 2). This degree of extraction is equalled only by exercising skeletal muscle, in which incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
3

Year Published

1962
1962
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(40 citation statements)
references
References 21 publications
(15 reference statements)
2
34
1
3
Order By: Relevance
“…Previous studies have shown that oxygen extraction ratios vary widely even in severe coronary artery disease (64,65) and appear to be a poor indicator of myocardial hypoxia (65). Presumably the scattered distribution of myocardial lesions, normal areas masking diseased areas, accounts for this insensitivity.…”
Section: Critique Of Experimental Methodsmentioning
confidence: 99%
“…Previous studies have shown that oxygen extraction ratios vary widely even in severe coronary artery disease (64,65) and appear to be a poor indicator of myocardial hypoxia (65). Presumably the scattered distribution of myocardial lesions, normal areas masking diseased areas, accounts for this insensitivity.…”
Section: Critique Of Experimental Methodsmentioning
confidence: 99%
“…This would, at least in theory, be manifested by appropriate changes in coronary venous oxygen content, the fraction of oxygen extracted and resting coronary blood flow (since arterial saturation tends to remain constant at normal levels of Po2). Such findings have not been described in either patients with the anginal syndrome and normal coronary arteriograms, nor in those with documented coronary artey disease (4,8,9,31).…”
Section: Methodsmentioning
confidence: 93%
“…Left ventricular failure was defined as an end-diastolic pressure greater than 10 mm Hg at rest, or a pulmonary wedge pressure greater than 12 mm Hg at rest or 17 on exercise. Coronary insufficiency (including angina pectoris alone) was defined as described elsewhere (17). No patients had diabetes mellitus, elevated fasting blood sugar,' or severe nutritional deprivation.…”
Section: Methodsmentioning
confidence: 99%
“…In most cases no premedication was necessary; in a few, 1 ml of a mixture of meperidine (25 mg per ml), Phenergan (6.25 mg per ml), and chlorpromazine (6.25 mg per ml) was given intramuscularly. Special care was taken to place the catheter deep in the proximal coronary sinus where homogeneity of sampling has been observed (17), and maximal representation of left ventricular events may be expected (20). Measurements of blood oxygen content were made immediately prior to and at least 3 minutes after onset of supine leg-raising; exercise was sufficient to raise mean myocardial oxygen consumption by 42 per cent (11.2 to 15.9 ml per 100 g per minute) and total body oxygen consumption by 112 per cent (145 to 307 ml per minute per m2).…”
Section: Methodsmentioning
confidence: 99%